Quantitative techniques - Lucey, T. (DP Publications, 1992)
Designed to provide a sound understanding of quantitative techniques, this manual is suitable for students on ICSA, ACCA, CIMA, CIPFA and BTEC higher level courses. It includes many exercises and examination questions both with and without answers. This edition has been revised and updated